2022
DOI: 10.7717/peerj.12933
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activities of durian (Durio zibethinusMurr.) pulp, seed and peel flour

Abstract: The unripe pulp, inner peel and seed of durian were used in this study. These are generally not considered edible and must be disposed of as waste. However, they are good sources of bioactive compounds. Flour extracts from the unripe pulp, inner peel, and seed of two durian (Durio zibethinus Murr.) varieties, namely, Monthong and Chanee, were analyzed chemically to determine their total phenolic content (TPC), antioxidant, and anti-inflammatory capacities. Chanee pulp (CPu) contained a higher TPC (5285.37 ± 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…6 Among their therapeutic attributes, the antioxidant and anti-inflammatory abilities of polyphenols are particularly noteworthy. 7,8 Focusing specifically on durian peel, previous studies have highlighted its exceptional nutritional composition and rich content of bioactive compounds. Feng et al noted the presence of triterpenoids and glycosides in durian peel, which have demonstrated anti-inflammatory effects via the inhibition of lipopolysaccharide-induced nitric oxide production in the RAW 264.7 cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Among their therapeutic attributes, the antioxidant and anti-inflammatory abilities of polyphenols are particularly noteworthy. 7,8 Focusing specifically on durian peel, previous studies have highlighted its exceptional nutritional composition and rich content of bioactive compounds. Feng et al noted the presence of triterpenoids and glycosides in durian peel, which have demonstrated anti-inflammatory effects via the inhibition of lipopolysaccharide-induced nitric oxide production in the RAW 264.7 cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they play a key role in regulating insulin secretion and utilization, leading to improved blood glucose levels. , Moreover, polyphenols contribute to the modulation of intestinal microbiota, thereby reducing intestinal inflammation and enhancing the integrity of the intestinal barrier, an important strategy for addressing gastrointestinal inflammation . Among their therapeutic attributes, the antioxidant and anti-inflammatory abilities of polyphenols are particularly noteworthy. , …”
Section: Introductionmentioning
confidence: 99%
“…Among parts of durian fruit, seeds and rinds have garnered attention for their nutritional profile and bioactive compounds (Zhan et al ., 2021; Charoenphun & Klangbud, 2022). Charoenphun & Klangbud (2022) reported that durian seeds and rinds contain high levels of phenolics, conferring antioxidant and anti‐inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among parts of durian fruit, seeds and rinds have garnered attention for their nutritional profile and bioactive compounds (Zhan et al ., 2021; Charoenphun & Klangbud, 2022). Charoenphun & Klangbud (2022) reported that durian seeds and rinds contain high levels of phenolics, conferring antioxidant and anti‐inflammatory properties. Despite their potential commercial utility, durian rinds are often discarded as waste once the edible portions are collected, leading to negative environmental consequences and loss of a valuable resource.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation